ANALISIS KIMIA SEPULUH JENIS BAMBU DARI JAWA TIMUR - Gusmailina Gusmailina; Suwardi Sumadiwangsa (Jurnal Penelitian Hasil Hutan, 1988)
Chemical analyses  of ten bamboo   species   from   East  Java  has  been  conducted.   The  analyses  comprised   of  the determination  of  cellulose,  lignin,  pentosan,  ash,  extractives  and  the solubility   in one percent  of sodium  hydroxide.  These analyses  were  commonly conducted    to  determine basic  characteristics and  ultimate uses  of  wood.The  analyses showed  that the  cellulose  content ranges from  42.4  - 53.6 percent, lignin from  19.8  - 26.6 percent, and  pentosan 17.5  - 21.5  percent.   The ash  and  silica  content   varies from  1.24 - 3.77 percent and  from  0.10  - 1.78 percent, respectively: The  solubility  in cold water ranges from  4.5 -  9.9 percent,  in hot  water from  5.3  - 11.8 percent,   in alcohol  benzene ( 1 :2)  from  0.9 - 6.9  percent, and  in one percent   sodium  hydroxide   solution  from  22.2  -  29.8 percent.Based  on  chemical  analyses, especially the  cellulose  content, the  bamboos  from  East  Java appeared  to  be a good material  for pulp  and paper  industry.